PENGARUH KEPUTUSAN INVESTASI, KEBIJAKAN DIVIDEN, DAN TINGKAT INFLASI TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Diah Triandika (2022)
In this study, a quantitative approach is to examine the effect of investment decision quantified by the Price Earnings Ratio (PER), dividend policy quantified by the Dividend Payout Ratio (DPR), and inflation rate quantified by the Price to Book Value (PBV) on the value of manufacturing sector companies listed on the Indonesia Stock Exchange (IDX) for 2018 to 2020. A total of 35 companies in the sector were observed using a purposive sampling approach from a population of 178 firms, yielding a total sample size of 105 firms. The data were analyzed using Microsoft Excel 2010 software, and hypothesis testing was performed using Panel Data Regression Analysis with a significance threshold of 5% using E-Views 12 software. The study's findings demonstrate that factors affecting investment decisions and dividend policy have a favorable effect on business value. However, The inflation rate variable has no influence on firm value.